The use of technology in a model of formative assessment - Alfonsa García López; Francisco García Mazarío (OmniaScience, 2016)
This work describes a formative assessment model for the Mathematical Analysis course taken by engineering students. It includes online questionnaires with feedback, a portfolio with weekly assignments, exams involving the use of mathematical software and a project to be completed in small groups of two or three students. The model has been perfected since 2009, and during the 2014-15 academic year the creation of a pilot online learning community was added. Based on Google+, it has been used for a peer assessment experiment involving student projects, among other uses.